2012
DOI: 10.14214/sf.61
|View full text |Cite
|
Sign up to set email alerts
|

Harvesting of short rotation coppice – harvesting trials with a cut and storage system in Germany

Abstract: Short rotation coppice (SRC) harvesting techniques are available in Germany, but broad experience and knowledge about machine performance and the related effective costs of harvesting operations are still missing. This information is crucial, as harvesting costs strongly influence the economic performance of the overall supply chain. Therefore, it was the aim of this study to collect and analyze productivity data of different harvesting systems for SRC. The combined cut and chip system on the one hand and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 13 publications
(12 reference statements)
0
24
0
1
Order By: Relevance
“…Other harvesting system would also be possible for poplar, for example wholetree harvest with chipping directly at field or at roadside [66]. A more efficient harvesting chain is important from an economic perspective [67,68], but will probably not have a large effect on the total climate impact as the fuel used in the harvest chain stand for small part of the total result.…”
Section: Discussionmentioning
confidence: 99%
“…Other harvesting system would also be possible for poplar, for example wholetree harvest with chipping directly at field or at roadside [66]. A more efficient harvesting chain is important from an economic perspective [67,68], but will probably not have a large effect on the total climate impact as the fuel used in the harvest chain stand for small part of the total result.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies (Schweier and Becker 2013) reported field performances of harvesting operations in the range of 0.51 ha h -1 to 0.97 ha h -1 for forage harvesters. Also, Schweier and Becker (2012b) reported field performances of 0.47 ha h -1 when willow SRCs were harvested with equipment capable to cut and store the biomass. They also pointed out that such an option would be more flexible, but it resulted in greater costs compared to cut and chip systems.…”
Section: Resultsmentioning
confidence: 99%
“…However, due to the need for extending rotation and diversifying tree species in short-rotation production, harvester prototypes capable of handling trees up to 15 cm at stump have been recently developed [66]. Oneprocess harvesting is often applied with short-rotation plantations; i.e., chipping takes place simultaneously with harvesting [67,68]. In consequence, the chips are wet, which implies a lower heating value and greater material losses in storage [69].…”
Section: Discussionmentioning
confidence: 99%